Petrography and geochemistry of clastic rocks within the Inthanon zone, northern Thailand: Implications for Paleo-Tethys subduction and convergence - Hidetoshi Hara (2018)
The provenance, source rock compositions, and sediment supply system for a convergence zone of the Paleo-Tethys were reconstructed based on the petrography and geochemistry of clastic rocks of the Inthanon Zone, northern Thailand. The clastic rocks are classified into two types based on field and microscopic observations, the modal composition of sandstone, and mineral compositions: (1) lithic sandstone and shale within mélange in a Permo-Triassic accretionary complex; and (2) Carboniferous quartzose sandstone and mudstone within the Sibumasu Block. Geochemical data indicate that the clastic rocks of the mélange were derived from continental island arc and continental margin settings, which correspond to felsic volcanic rocks within the Sukhothai Zone and quartz-rich fragments within the Indochina Block, respectively. The results of a mixing model indicate the source rocks were approximately 35% volcanic rocks of the Sukhothai Zone and 65% craton sandstone and upper continental crust of the Indochina Block. In contrast, Carboniferous quartzose sedimentary rocks within the Sibumasu Block originated from a continental margin, without a contribution from volcanic rocks. In terms of Paleo-Tethys subduction, a continental island arc in the Sukhothai Zone evolved in tandem with Late Permian-Triassic forearc basins and volcanic activity during the Middle-early Late Triassic. The accretionary complex formed contemporaneously with the evolution of continental island arc during the Permo-Triassic, supplied with sediment from the Sukhothai Zone and the Indochina Block. © 2012 Elsevier Ltd.